Prinsip Al-Qur’an dalam menanamkan nilai-nilai spiritual kepada anak: Kajian Tematik kisah Nabi Musa dalam surah Al-Qashash - Khoirotul Jannah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The challenge of instilling spiritual values in children, such as the lack of effective methods for Islamic character education and the negative impact of technology, often hinders the formation of Islamic character. This study aims to explore the spiritual values in the story of Prophet Musa in Surah Al-Qasas and identify relevant Qur'anic principles. The method employed is a literature review with a thematic exegesis approach, using Al-Maraghi's tafsir to descriptively analyze related verses. The findings reveal spiritual values such as trust in Allah (tawakkal), sincerity (ikhlas), compassion (rahmah), and belief in Allah's promises, as well as key principles like divine communication, value transmission through exemplary behavior, integration of faith and action, and wisdom in decision-making. These values and principles are relevant for application in Islamic character education in the modern era to cultivate a generation with strong faith and character based on Islamic values. Overall, the story of Prophet Musa provides significant guidance in shaping Islamic character in today's generation.